ANALISIS DAYA TARIK KULINER LOKAL SEBAGAI REPRESENTASI IDENTITAS BUDAYA KULINER DI PASAR KLOJEN MALANG - Ratukasih Ratukasih (Jurnal Pariwisata Tawangmangu, 2026)
Local cuisine plays a significant role in shaping cultural identity at Klojen Market in Malang. Culinary tourism is a dynamic segment of the tourism industry because it offers authentic experiences through local foods that reflect a destination's social and cultural values. Klojen Market, a traditional market revitalized with a modern concept, offers a blend of traditional culinary practices and contemporary dining spaces. This study aims to analyze how the appeal of local cuisine at Klojen Market reflects Malang's cultural identity. A qualitative descriptive approach was used to understand the experiences, perceptions, and social interactions within culinary practices at the market. Data were collected through in-depth interviews, observations, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion. The results indicate that the appeal of local cuisine is shaped by five key aspects: local ingredients, presentation, flavor, uniqueness, authenticity, and cultural value. Culinary practices serve not only as consumption activities but also as cultural expressions reflected in habitus, social interactions, and symbolic meanings. These findings align with Bourdieu's theory of distinction in explaining the relationship between consumption and cultural identity. In conclusion, Klojen Market serves as a vital space for representing the local culinary culture and supporting the development of sustainable culinary tourism.